Inside the American couple : new thinking/new challenges - Yalom, Marilyn; Carstensen, Laura L. (Berkeley : University of California Press, 2002)
One of the most fundamental human urges is to form a pair. Despite many tendencies that threaten traditional marriage and even make committed cohabitation problematic, very few people live through adulthood without at least one lengthy relationship, and up to ninety percent of Americans marry at least once in their lives.
Biblical models: from Adam and Eve to the bride of Christ / Marilyn Yalom -- Dearest friend: the marriage of Abigail and John Adams / Edith B. Gelles -- "The thing bartered": love economics and the Victorian couple / Kate Washington -- "Boston marriage" among lesbians: are we a couple if we're not having sex? / Esther D. Rothblum -- "You'll never walk alone": lesbian and gay weddings and the authenticity of the same-sex couple / Ellen Lewin -- The couple at home: education's contribution / Nel Noddings -- When one of us is ill: scenes from a partnership / Mary Felstiner -- Wives and husbands working together: law partners and marital partners / Cynthia Fuchs Epstein -- Grounds for marriage: reflections and research on an institution in transition / Arlene Skolnick -- Divorce, American style / Deborah L. Rhode -- What's a wife worth? / Myra H. Strober -- Toward an understanding of Asian American interracial marriage and dating / Jeanne L. Tsai, Diane E. Przymus, and Jennifer L. Best -- Arranged marriages: what's love got to do with it? / Monisha Pasupathi -- Marriage in old age / Susan Turk Charles and Laura L. Carstensen.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Couples -- United States; Interpersonal relations -- United States; Couples -- États-Unis.; PSYCHOLOGY -- Human Sexuality; SELF-HELP -- Sexual Instruction; SOCIAL SCIENCE -- Gender Studies; Couples; Interpersonal relations; United States